A New Strategy for the Rapid Identification and Validation of the Direct Targets of Aconitine-Induced Cardiotoxicity - Wei J; Fan S; Yu H; Shu L; Li Y (Dove Medical Press, 2021)
Jinxia Wei,* Simiao Fan,* Hongxin Yu,* Lexin Shu, Yubo Li School of Chinese Materia Medica, Tianjin University of Traditional Chinese Medicine, Tianjin, People's Republic of China*These authors contributed equally to this workCorrespondence: Yubo LiSchool of Chinese Materia Medica, Tianjin University of Traditional Chinese Medicine, No. 10, Poyang Lake Road, West Zone, Tuanbo New City, Jinghai District, Tianjin, 301617, People's Republic of ChinaTel +86-22-59591974Email yaowufenxi001@sina.comBackground: The interaction of small molecules with direct targets constitutes the molecular initiation events of drug efficacy and toxicity. Aconitine, an active compound of the Aconitum species, has various pharmacological effects but is strongly toxic to the heart. The direct targets of aconitine-induced cardiotoxicity remain unclear.Methods: We predicted the toxic targets of aconitine based on network pharmacology and followed a novel proteomic approach based on the "drug affinity responsive target stability" technology combined with LC-MS/MS to identify the direct targets of aconitine. The identified targets were analysed from the perspective of multilevel and multidimensional bioinformatics through a network integration method. The binding sites were investigated via molecular docking to explore the toxicity mechanism and predict the direct targets of aconitine. Finally, atomic force microscopy (AFM) imaging was performed to verify the affinity of aconitine to the direct targets.Results: PTGS2, predicted by network pharmacology as a toxic target, encodes cyclooxygenase 2 (COX-2), which is closely related to myocardial injury. Furthermore, cytosolic phospholipase A2 (cPLA2) is the upstream signal protein of PTGS2, and it is a key enzyme in the metabolism of arachidonic acid during an inflammatory response. We determined cPLA2 as a direct target, and AFM imaging verified that aconitine could bind to cPLA2 well; thus, aconitine may cause the expression of PTGS2/COX-2 and release inflammatory factors, thereby promoting myocardial injury and dysfunction.Conclusion: We developed a complete set of methods to predict and verify the direct targets of aconitine, and cPLA2 was identified as one. Overall, the novel strategy provides new insights into the discovery of direct targets and the molecular mechanism of toxic components that are found in traditional Chinese medicine.Keywords: aconitine, cardiotoxicity, direct targets, drug affinity responsive target stability technology, atomic force microscopy